2008
DOI: 10.1152/ajpgi.00468.2007
|View full text |Cite
|
Sign up to set email alerts
|

Topical transplantation of mesenchymal stem cells accelerates gastric ulcer healing in rats

Abstract: Mesenchymal stem cells (MSCs), a subpopulation of adult somatic stem cells, are an attractive stem cell source in regenerative medicine because of their multipotentiality. We examined the effects of MSC transplantation on gastric ulcer healing. Putative MSCs, isolated from bone marrow aspirates of male rats by dish adherence and expanded in culture, were characterized by flow cytometry and reverse transcription-polymerase chain reaction. Gastric ulcers were induced by serosal application of acetic acid on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…After 3 weeks incubation, cells were fixed with 4% paraformaldehyde, and stained with Oil red O (Fluka) for detecting adipocytes containing lipid vacuoles or with Alizarin red (Fluka) to detect osteocytes containing calcium deposits. 9,31 All results of these characterisations (Supplementary Figure S5) consistently demonstrated that the collected cells were MSCs.…”
Section: Isolation Culture and Characterization Of Rat Bone Marrow-mentioning
confidence: 54%
See 1 more Smart Citation
“…After 3 weeks incubation, cells were fixed with 4% paraformaldehyde, and stained with Oil red O (Fluka) for detecting adipocytes containing lipid vacuoles or with Alizarin red (Fluka) to detect osteocytes containing calcium deposits. 9,31 All results of these characterisations (Supplementary Figure S5) consistently demonstrated that the collected cells were MSCs.…”
Section: Isolation Culture and Characterization Of Rat Bone Marrow-mentioning
confidence: 54%
“…9,31 Adipogenic differentiation medium was α-minimal essential medium supplemented with 100 μmol/l isobutyl methylxathine (SigmaAldrich, Dorset, UK), 60 μmol/l indomethacin (Fluka, Dorset, UK), 1 μg/ml insulin (Sigma-Aldrich), and 0.5 μmol/l hydrocortisone (SigmaAldrich). Osteogenic differentiation medium was α-minimal essential medium supplemented with 0.1 μmol/l dexamethasone, 10 mmol/l β-glycerophosphate, and 0.05 mmol/l ascorbic acid (all from SigmaAldrich).…”
Section: Isolation Culture and Characterization Of Rat Bone Marrow-mentioning
confidence: 99%
“…Some studies have shown that MSCs could also achieve the biological effects by secreting VEGF. VEGF secreted by MSCs has been used in gastric ulcer and oral ulcer healing (El-Menoufy et al 2010;Hayashi et al 2008), in murine ischemic limbs leading to an increase in vessel density (Hoffmann et al 2010), in inhibiting the apoptosis of lung cells (Zhen et al 2010), in facilitating neurological function (Deng et al 2010), enhancing the repair and regeneration of critical sized bone defects (Kanczler et al 2010) and improving cardiac function in failing rat hearts (Tao et al 2009). Therefore, the VEGF 165 gene is the best target gene in gene therapy for promoting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in liver function found in the previously mentioned studies seem not to be mainly mediated by parenchymal cell replacement, but by paracrine mechanisms promoting survival of endogenous hepatocytes and proliferation of hepatocyte progenitors. 188,230 MSCs could therefore exert their effects through secretion of cytokines 123,232 and growth factors, such as HGF 185 or nerve growth factor. 233 While the former can trigger hepatocyte anti-apoptotic mechanisms, 234 or inhibition of fibrogenesis by exportation of Smad3, 235 the latter might result in HeSC programmed cell death.…”
Section: Mscs and Their Anti-fibrotic Potentialmentioning
confidence: 99%